APLIKASI ABU SEKAM PADI DAN PUPUK KANDANG DI LAHAN GAMBUT DAN PENGARUHNYA TERHADAP PERTUMBUHAN DAN PRODUKSI PADI GOGO (Oryza sativa L.) DI AREAL GAWANGAN KELAPA SAWIT - Araif Jaelani; Jurnawaty Sjofjan; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rice is plant resulting rice which become main food to people but production of rice still low and need an effort to increase the production of rice. The research aims to obtain the best dosage of rice husk ash with manure on the growth and yield of field rice in peatland at hall of oil palm area. The research was conducted at the experimental farm of the Agricultural Faculty University of Riau, Rimbo Panjang Kampar from August-December 2014. The research was conducted completely a Randomized Block Design (RBD) factorial consisting of 2 factors with 3 replications. The first factor are: Aplication of rice husk ash with 4 level (tons/ha) namely : A0 (0), A1 (2.5), A2 (5), A3 (7.5) and the second factor are : Manure application with 3 levels (tons / ha), namely: K0 (0), K1 (5), K2 (10). The data obtained by analysis of variance (ANOVA) was tested further by Duncan’s New Multiple Range Test (DNMRT) at the level of 5%. The results showed that the application of rice husk ash 7.5 tons / ha and manure 5 tons/ha gave the highest yield of dry grain is 1056.67 g (equal to 3:52 tons / ha). Keywords: Rice Husk Ash, Manure, Field Rice, Hall of Oil Palm Area, Peatland